Upaya Peningkatan Penjualan Produk UMKM Di Kecamatan Mejayan Kabupaten Madiun Melalui Platform Lapak Daya BTPN Syariah - Putri, Intan Windyar Handono; Wijaya, Anggita Langgeng (Universitas PGRI Madiun, 2026)
Rapid technological developments encourage MSMEs to adapt. Reliable and competitive MSMEs must utilize technology and information systems efficiently. In an effort to increase the marketing and sales of their products, MSMEs in Mejaya District, Madiun Regency, face challenges in fully leveraging digitalization. This community service activity aims to provide MSMEs with knowledge and training on the use of information technology in product marketing. The method is to provide training and create advertisements on Instagram. Before the training, MSME participants took an initial test, and after the training, they were given a final test. The results of the community service activity showed an increase in understanding and skills of MSMEs in Mejayan District in the use of digital technology for product marketing purposes. The results of this activity are expected to support efforts to increase MSME product sales in Mejayan District, Madiun Regency.